0801 Changes in Sleep Habits as a Function of Age in Late Adolescence. (12th April 2019) - Gaudreault, Pascale; Brunet, Jean-François; Godin, Roxanne; Michaud, Frédérick; Green-Demers, Isabelle; Forest, Geneviève
Abstract: Introduction: As they grow older, adolescents tend to go to bed later, but still wake-up early to go to school during weekdays. It has also been found that boys and girls have different sleep habits. However, few studies have looked at the changes in these sleep habits in both genders across adolescence. This was the aim of the present study. Methods: 654 adolescents (269boys; 385girls; 14-17y) completed questionnaires on sleep habits. First, repeated measures ANOVAs were performed on the sleep midpoint during school nights and during weekends in order to compare the sleep patterns of boys and girls across age (14 to 17 years old). Secondary analysis were then performed on bedtimes and wake-up times during weekends using repeated measures ANOVAs to compare only the 16 and 17 years old boys and girls. Results: A significant Gender X Age interaction was found [ F (3, 4.567)=2.714, p <.05] for the sleep midpoint during weekends. Single comparison follow-up analysis using independent t-tests showed thatat 16y, the boys' sleep midpoint on weekends was significantly later than the girls' (5h23±1h24 vs 4h55±1h10, respectively; t (206)=2.622, p =.01). This finding led us to investigate the sleep schedules of older teenagers. There was no difference in bedtimes during weekends between 16 and 17 year old boys and girls. However, there was a significant Gender X Age [ F (1, 12.087)=4, 466, p <.05] interaction for the wake-up times on weekends. Results show that 16 and 17 years old girls continued to gradually delay their wake-up times as they grow older. On the other hand, at 17, boys show a significant advance in their wake-up times. Conclusion: Our results suggest that sleep habits are changing differently in boys and girls across adolescence. Further studies should look at possible explanations for these gender differences. For example, it could be hypothesized that older boys are more likely to have a job than older girls, which could explain why they wake-up earlier on weekends. Our results underline the importance of studying weekend sleep habits in late teens, as it may have a significant impact on their overall sleep. Support (If Any): N/A